Post-war hospital problems (letter) - Daily Herald ; Scottish Union of Bakers, Confectioners and Bakery Workers
1943-08-31 1943 1940s 6 pages - 2 - whole thing of course is confidential and I am not mentioning the matter to anybody else. You will be aware of the Labour Party policy on hospitals with which we are substantially in agreement. Whilst regional arrangements are all right I think it would be a great mistake to give them executive authority. It will I imagine be impossible to build up a properly co-ordinated service unless there is a national standard of service and effective controlling machinery. Within that it seems to me the regions will have plenty of opportunity of exercising their imagination and ingenuity but if they have control you are bound to get a continuance of the unequal development and unsatisfactory service which exists at present. The terms of reference, whilst designed to keep the report more or less on the lines of the government's policy, would not I imagine prevent an opposite point of view being expressed. It may be through not having been able to read the document closely that I have missed some arguments which meet the points I am expressing and in any case I know you will expect me to express a frank view in a personal and confidential way. I am much obliged to you for letting me see the document. All good wishes, Yours sincerely, Secretary Social Insurance Department 292/842/2/122